Shaping Tourism Strategies through Local Perceptions: A Case Study of Muharraq - Afaf Ebrahim Mohamed; Islam Hamdy Elghonaimy (Alanya Üniversitesi, 2025)
Bahrain, a longstanding tourist destination in the Gulf region, has seen its economy benefit significantly from tourism. However, the improper development of tourism has led to negative impacts on urban tourism in historic areas, risking the loss of authenticity. This study aims to explore factors influencing the development of tourism strategies in Muharraq city, focusing on residents' perceptions. A qualitative approach was used, including a comprehensive literature review, interviews with residents to capture their views on tourism-related issues, and a self-administered questionnaire with key officials and stakeholders. The study identifies critical factors affecting tourism development and offers recommendations for enhancing cultural tourism in Muharraq. The findings provide valuable insights for policymakers to create sustainable strategies that balance economic growth with cultural preservation, ensuring that Muharraq remains a culturally vibrant city while promoting sustainable urban tourism. This research contributes to the broader field of urban tourism studies by highlighting the importance of local perceptions and participatory approaches in shaping effective tourism policies. By addressing key elements that influence tourism development, the study supports the creation of strategies that safeguard heritage while fostering sustainable growth in one of Bahrain's most culturally significant cities.